Norms for Hispanic older adults on the National Alzheimer's Coordinating Center's Uniform Data Set 3.0 Neuropsychological Battery. (31st December 2021) - Rosado‐Bruno, Mónica; Reyes, Marcos; Kiselica, Andrew M
Abstract: Background: Limited availability of norms for cognitive tests among older adult Hispanic individuals leads to problems with diagnosis, prognosis, and intervention. Moreover, few studies have evaluated the impact of language of test administration (i.e., Spanish vs. English) on test performance in this group. Method: Multivariate regressions were used to evaluate the impact of demographic factors on neuropsychological test performance in a sample of cognitively normal individuals tested with the Uniform Data Set 3.0 ( n = 445). Demographically adjusted norms were created for both the overall Hispanic sample, as well as for regional cultural groups, using a regression‐based approach. Formulas were incorporated into a user‐friendly calculator for easy use in clinical settings and future research. Result: Age demonstrated a negative relationship with all cognitive scores, inversely to education. Female sex and English testing language were significantly associated with better performance on multiple tests. However, the contrary effect was found with respect to the Multilingual Naming Test. Generally consistent results were reported in assessed regional cultural subgroups. Conclusion: Results provide much needed methods to assist with interpreting cognitive test data among older Hispanic adults. Language of test administration emerged as a critical factor for score interpretation, with scores favoring English speakers.